2019
DOI: 10.1002/jctb.6238
|View full text |Cite
|
Sign up to set email alerts
|

V2O5/RGO/Pt nanocomposite on oxytetracycline degradation and pharmaceutical effluent detoxification

Abstract: BACKGROUND: Antibiotics have been identified as significant pollutants owing to their adverse impact on the environment through the development of antibiotic-resistant bacteria. In a previous study, an e-waste-based reduced graphene oxide-V 2 O 5 -platinum (RGOV-Pt(1%)) nanocomposite was prepared and subsequently used for the photocatalytic degradation of oxytetracycline (OTC), a tetracycline group of antibiotics. RESULTS:This study aimed to assess the impact of additives such as H 2 O 2 , NaCl, Na 2 CO 3 , et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…46 The wileyonlinelibrary.com/jctb presence of chloride anions blocks the active sites at the catalyst-BTEX interface and inhibits the efficiency of the photocatalytic degradation processes. 46,47 The decrease in the degradation of BTEX in the presence of carbonate ions is due to the hydroxyl scavenging property of carbonate ions, 48 as in Eqn (6) 48,49 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The wileyonlinelibrary.com/jctb presence of chloride anions blocks the active sites at the catalyst-BTEX interface and inhibits the efficiency of the photocatalytic degradation processes. 46,47 The decrease in the degradation of BTEX in the presence of carbonate ions is due to the hydroxyl scavenging property of carbonate ions, 48 as in Eqn (6) 48,49 :…”
Section: Resultsmentioning
confidence: 99%
“…Chloride ions are very stable and are not readily oxidizable . The presence of chloride anions blocks the active sites at the catalyst–BTEX interface and inhibits the efficiency of the photocatalytic degradation processes …”
Section: Resultsmentioning
confidence: 99%
“…The composite also showed sufficient stability, with up to 100% efficiency still recorded after 3 cycles of usage. Similarly, Mohan, et al [151] reported the degradation of oxytetracycline by V 2 O 5 /rGO/Pt composites. The study focused on the effect of additives such as H 2 O 2 , Na 2 CO 3 , ethanol, persulfate and NaCl on the degradation efficiency of the photocatalyst.…”
Section: Noble Metal Based Photocatalystsmentioning
confidence: 88%
“…Conventional treatments such as physical and chemical methods, biodegradation, chemical and electrochemical oxidation have been applied for the degradation of these different drugs 1,3,8 . However, these processes don't lead to a total mineralization of this products but most of the time transform them from one phase to another 9 . Hence, Advanced Oxidation processes (AOP), based on the production of highly reactive chemical including hydroxyl and superoxide anions radicals, have appeared as a new and performant technique for the total removal and mineralization of numerous emergent pollutants 4,5,10 .…”
Section: Introductionmentioning
confidence: 99%